Increased In Vivo Exposure of N-(4-Hydroxyphenyl) Retinamide (4-HPR) to Achieve Plasma Concentrations Effective against Dengue Virus - Alexander J. Martin; David M. Shackleford; Susan A. Charman; Kylie M. Wagstaff; Christopher J. H. Porter; David A. Jans (MDPI AG, 2023)
N-(4-hydroxyphenyl) retinamide (4-HPR, or fenretinide) has promising in vitro and in vivo antiviral activity against a range of flaviviruses and an established safety record, but there are challenges to its clinical use. This study evaluated the in vivo exposure profile of a 4-HPR dosage regime previously shown to be effective in a mouse model of severe dengue virus (DENV) infection, comparing it to an existing formulation for human clinical use for other indications and developed/characterised self-emulsifying lipid-based formulations of 4-HPR to enhance 4-HPR in vivo exposure. Pharmacokinetic (PK) analysis comprising single-dose oral and IV plasma concentration-time profiles was performed in mice; equilibrium solubility testing of 4-HPR in a range of lipids, surfactants and cosolvents was used to inform formulation approaches, with lead formulation candidates digested in vitro to analyse solubilisation/precipitation prior to in vivo testing. PK analysis suggested that effective plasma concentrations could be achieved with the clinical formulation, while novel lipid-based formulations achieved > 3-fold improvement. Additionally, 4-HPR exposure was found to be limited by both solubility and first-pass intestinal elimination but could be improved through inhibition of cytochrome P450 (CYP) metabolism. Simulated exposure profiles suggest that a b.i.d dosage regime is likely to maintain 4-HPR above the minimum effective plasma concentration for anti-DENV activity using the clinical formulation, with new formulations/CYP inhibition viable options to increase exposure in the future.